Tinjauan Literatur: Pengaruh Kebahagiaan di Tempat Kerja terhadap Perilaku Kerja Inovatif di Sektor Kesehatan - Endah Wulan Safitri (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the influence of workplace happiness on innovative work behavior in the healthcare sector using a qualitative approach with a literature review method. Data were obtained from scholarly journal articles and credible publications that were carefully selected based on their relevance to the research focus. The findings indicate that workplace happiness positively contributes to enhancing innovative work behavior by strengthening psychological well-being, fostering intrinsic motivation, and increasing employee engagement in idea development and problem-solving processes. Both hedonic and eudaimonic happiness influence creativity, job satisfaction, and affective commitment, thereby encouraging innovation within organizational practices. Internal factors such as psychological capital and external factors such as organizational support further reinforce this relationship. In the healthcare context, improving employee happiness significantly impacts service quality, work efficiency, and the development of sustainable innovation in healthcare services.